Peripartum Cardiomyopathy. Medical Support Strategy - Siromakha, Sergii O.; Davydova, Iuliia V.; Nevmerzhytska, Lidiia O.; Lymanska, Alisa Yu. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Peripartum cardiomyopathy (PPCM) is an idiopathic myocardial insufficiency that occurs in the absence of any diagnosed heart disease during the last month of pregnancy or during the first 5 months after delivery. The aim. To improve immediate and long-term maternal outcomes in patients with PPCM by establishing an optimal strategy for its diagnosis, treatment, delivery and medical support during the postpartum period. Materials and methods. The article presents the experience of multidisciplinary medical care for 11 pregnant wo-men and postpartum women with dilated cardiomyopathy (DCM) on the basis of the National Amosov Institute of Cardio-vascular Surgery and the Institute of Pediatrics, Obstetrics and Gynecology named after acad. O. M. Lukianova of NAMS of Ukraine. After the differential diagnosis, 8 women were defined as patients with PPCM, and 3 women had family history of the disease (DCM in relatives). All the patients were examined according to the protocol using the history, examination, and instrumental and laboratory findings. Results. After in-hospital treatment there was an increase in the left ventricular ejection fraction (LVEF) in the group of patients with PPCM from 28.3 ± 9.3% to 37.6 ± 7.6% and a decrease in end-diastolic volume (EDV) from 196.7 ± 47.7 ml to 181.3 ± 59.7 ml, end-systolic volume (ESV) from 104.25 ± 33.3 ml to 94.2 ± 35.1 ml. In four cases, patients with severe left ventricular (LV) dysfunction underwent urgent preterm Cesarean section in the second trimester of pregnancy. There were no early maternal losses, there were two perinatal losses of extremely premature infants (16 and 27 weeks of gesta-tion). In the follow-up period (23.5 ± 11.6 months), LVEF further increased up to 42.9 ± 8.4% and EDV and ESV decreased up to 170.1 ± 49.5 and 82.7 ± 40.6 ml, respectively. In 7 (87.5%) patients with PPCM, a significant improvement in clini-cal condition and pumping function of the heart was registered at the time of discharge from the hospital, and there was further improvement in the indicators for another 12 months, but complete recovery of cardiac function was achieved only in 3 (37.5%) patients. In patients from the group of family type DCM, complete recovery of LV myocardial function was not observed in any of the 3 studied cases. The article discusses the timing of the occurrence and diagnosis of PPCM, the main clinical, instrumental and labora-tory signs of the pathology, methods of cardiological, cardiosurgical and obstetric support of such pregnant women. Conclusions. The terms of the onset of PPCM manifestations may be wider (earlier) according to our observations and should be the subject of further research. The strategy of medical care for pregnant women doesn’t particularly depend on the type of DCM. However, obstetric tactics aimed at early delivery of a patient with PPCM with severe myocardial insufficiency are feasible in combination with interruption of lactation and in most cases allow to achieve compensation of circulation and partial recovery of LV function. Prescription of bromocriptine for this purpose seems appropriate. The use of repeated courses of levosimendan in patients with PPCM is feasible and helps to improve the LV function in the early postpartum period.